Safety and immunogenicity of the chlamydia vaccine candidate CTH522 adjuvanted with CAF01 liposomes or aluminium hydroxide: a first-in-human, randomised, double-blind, placebo-controlled, phase 1 trial - Abraham,S; Juel,HB; Bang,P; Cheeseman,HM; Dohn,RB; Cole,T; Kristiansen,MP; Korsholm,KS; Lewis,D; Olsen,AW; McFarlane,LR; Day,S; et al. (Lancet Infectious Diseases, 2019)
BACKGROUND: Chlamydia is the most common sexually transmitted bacterial infection worldwide. National screening programmes and antibiotic treatment have failed to decrease incidence, and to date no vaccines against genital chlamydia have been tested in clinical trials. We aimed to assess the safety and immunogenicity, in humans, of a novel chlamydia vaccine based on a recombinant protein subunit (CTH522) in a prime-boost immunisation schedule. METHODS: This phase 1, first-in-human, double-blind, parallel, randomised, placebo-controlled trial was done at Hammersmith Hospital in London, UK, in healthy women aged 19-45 years. Participants were randomly assigned (3:3:1) to three groups: CTH522 adjuvanted with CAF01 liposomes (CTH522:CAF01), CTH522 adjuvanted with aluminium hydroxide (CTH522:AH), or placebo (saline). Participants received three intramuscular injections of 85 μg vaccine (with adjuvant) or placebo to the deltoid region of the arm at 0, 1, and 4 months, followed by two intranasal administrations of 30 μg unadjuvanted vaccine or placebo (one in each nostril) at months 4·5 and 5·0. The primary outcome was safety and the secondary outcome was humoral immunogenicity (anti-CTH522 IgG seroconversion). This study is registered with Clinicaltrials.gov, number NCT02787109. FINDINGS: Between Aug 15, 2016, and Feb 13, 2017, 35 women were randomly assigned (15 to CTH522:CAF01, 15 to CTH522:AH, and five to placebo). 32 (91%) received all five vaccinations and all participants were included in the intention-to-treat analyses. No related serious adverse reactions were reported, and the most frequent adverse events were mild local injection-site reactions, which were reported in all (15 [100%] of 15) participants in the two vaccine groups and in three (60%) of five participants in the placebo group (p=0·0526 for both comparisons). Intranasal vaccination was not associated with a higher frequency of related local reactions (reported in seven [47%]